2009
DOI: 10.1002/smll.200800461
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Dependent Cytotoxicity of Monodisperse Silica Nanoparticles in Human Endothelial Cells

Abstract: The effect that monodisperse amorphous spherical silica particles of different sizes have on the viability of endothelial cells (EAHY926 cell line) is investigated. The results indicate that exposure to silica nanoparticles causes cytotoxic damage (as indicated by lactate dehydrogenase (LDH) release) and a decrease in cell survival (as determined by the tetrazolium reduction, MTT, assay) in the EAHY926 cell line in a dose-related manner. Concentrations leading to a 50% reduction in cell viability (TC(50)) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
371
7
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(419 citation statements)
references
References 32 publications
31
371
7
3
Order By: Relevance
“…The binding of GQDs to the RBC molecule can be linked to the small particle size of GQDs which is also linked to the strong electrostatic interactions with phosphatidylcholine lipids present on the surface of the RBC membrane [72]. In agreement with our findings, the size-dependent cytotoxicity on human RBCs and mammalian cells has been reported earlier testing other nanoparticles, such as silica [73,74] and latex ones [75]. In addition, studies on hemolytic activity of silver nanoparticles showed that the release of low silver ion concentrations leads to the death of RBC molecule [76].…”
Section: Hemolytic Activitysupporting
confidence: 91%
“…The binding of GQDs to the RBC molecule can be linked to the small particle size of GQDs which is also linked to the strong electrostatic interactions with phosphatidylcholine lipids present on the surface of the RBC membrane [72]. In agreement with our findings, the size-dependent cytotoxicity on human RBCs and mammalian cells has been reported earlier testing other nanoparticles, such as silica [73,74] and latex ones [75]. In addition, studies on hemolytic activity of silver nanoparticles showed that the release of low silver ion concentrations leads to the death of RBC molecule [76].…”
Section: Hemolytic Activitysupporting
confidence: 91%
“…SiO2 nanoparticles caused damage to EAHY926 line cells, and here it should be noted that analog particles of sub-micron size (100-300nanometers) were not toxic [26]. Nano-sized SiO2 with particles diameter equal to 10 and 30, but not 80 nanometers suppressed differentiation into cardiac hystiocytes in stem cells culture of a mouse embryo [18].…”
mentioning
confidence: 70%
“…The smaller the NPs, the greater the contact with the surrounding medium at the interface and the more degradable the NPs. Unfortunately, such small particles cause higher cell toxicity and hemolytic activity [8][9][10][11]. In contrast, the degradation of MSNPs is not size dependent in a size range of 20 to 80 nm diameter, as it is mainly caused by the enlarged surface area due to the pores [7].…”
Section: Introductionmentioning
confidence: 99%